Human α1‐antitrypsin modifies B‐lymphocyte responses during allograft transplantation. Issue 3 (3rd October 2013) - Mizrahi, Mark; Cal, Pablo; Rosenthal, Martin; Ochayon, David; Shahaf, Galit; Kaner, Ziv; Kachker, Peter; Lewis, Eli C.
Summary B‐lymphocyte activities are associated with allograft rejection. Interleukin‐10 (IL‐10) ‐expressing B cells, however, exhibit regulatory attributes. Human α1‐antitrypsin (hAAT), a clinically available anti‐inflammatory circulating glycoprotein that rises during acute‐phase responses, promotes semi‐mature dendritic cells and regulatory T (Treg) cells during alloimmune responses. Whether B lymphocytes are also targets of hAAT activity has yet to be determined. Here, we examine whether hAAT modulates B‐cell responses. In culture, hAAT reduced the lipopolysaccharide‐stimulated Ki‐67+ B‐cell population, IgM release and surface CD40 levels, but elevated IL‐10‐producing cells 1.5‐fold. In CD40 ligand‐stimulated cultures, hAAT promoted a similar trend; reduction in the Ki‐67+ B‐cell population and in surface expression of CD86, CD80 and MHCII. hAAT increased interferon‐γ‐stimulated macrophage B‐cell activating factor (BAFF) secretion, and reduced BAFF‐receptor levels. Draining lymph nodes of transgenic mice that express circulating hAAT (C57BL/6 background) and that received skin allografts exhibited reduced B‐lymphocyte activation compared with wild‐type recipients. BSA‐vaccinated hAAT transgenic mice exhibited 2.9‐fold lower BSA‐specific IgG levels, but 2.3‐fold greater IgM levels, compared with wild‐type mice. Circulating Treg cells were 1.3‐fold greater in transgenic hAAT mice, but lower in B‐cell knockout (BKO) and chimeric hAAT–BKO mice, compared with wild‐type mice. In conclusion, B cells are cellular targets of hAAT. hAAT‐induced Treg cell expansion appears to be B‐cell‐dependent. These changes support the tolerogenic properties of hAAT during immune responses, and suggest that hAAT may be beneficial in pathologies that involve excessive B‐cell responses.